Perkembangan Digital Media di Dunia - Muqsith, Munadhil Abdul (UIN Jakarta, 2021)
Every day, the amount of traffic on the internet grows. This is due to the fact that internet network backbone providers are becoming more promising as ISPs pursue backbones that are directly connected to countries whose network access goes directly to various countries. This paper investigates the rapid growth of digital developments in today's modern era. As a result of this need, other underground cable facilities that cross the ocean and connect regions have been built.Keywords: Internet; Media; Digital